Building a Restaurant-Specific Sentiment Lexicon via Probability Theory - Melo, Tiago de (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2021: Proceedings of the 27th Brazilian Symposium on Multimedia and the Web, 2021)
Online user reviews written in Portuguese language are widely used by native speakers from several countries for decision-making and a large amount user reviews are available on the Web. However, only few studies on Portuguese sentiment analysis are reported as there is a lack of resources including domain-specific sentiment lexical collections. In this paper, we present an effective method for building a set of lexicons in restaurant domain for Portuguese language. The experiments on a large data collection of user reviews illustrate that our method significantly outperforms several alternative previous approaches of building domain-specific sentiment lexicon.